Some demographic aspects of population aging in Malaysia - Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
One of the most important demographic events occurred in the 21st century is the increasing number of older persons in community through a demographic event, known as demographic aging, or population aging.There are signs that population of Malaysia is starting to aging.As the percentage of older population continues to increase, the need for extensive and current information on this older population increases.This article attempts to review some emerging issues that form the context of demographic aging in Malaysia.To meet the objective, this article uses secondary data as its main devices.It reviews some published materials and highlights some emerging issues in terms of demographic aspects.Secondary data in this discussion are derived from the report of Population and Housing Census of Malaysia and various books on demographic aging in Malaysia.There are some related issues can be analyzed, include number of older people, median ages, dependency ratio, aging index and geographic distribution.From the discussion it is clear that the population of Malaysia is moving towards aging.